2005
DOI: 10.1038/sj.jcbfm.9600108
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 Overexpression Leads to Further Water Accumulation and Brain Edema after Middle Cerebral Artery Occlusion via Aquaporin 4 Expression in Astrocytic End-Feet

Abstract: Stroke patients have increased levels of endothelin-1 (ET-1), a strong vasoconstrictor, in their plasma or cerebrospinal fluid. Previously, we showed high level of ET-1 mRNA expression in astrocytes after hypoxia/ischemia. It is unclear whether the contribution of ET-1 induction in astrocytes is protective or destructive in cerebral ischemia. Here, we generated a transgenic mouse model that overexpress ET-1 in astrocytes (GET-1) using the glial fibrillary acidic protein promoter to examine the role of astrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
158
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(166 citation statements)
references
References 70 publications
(121 reference statements)
7
158
0
1
Order By: Relevance
“…In the past, several compounds that aim at restoring the endothelin-1/nitric oxide imbalance have been successfully applied to reduce microcirculatory disturbances and liver tissue damage. 18,19,54,70,71 Atrasentan is effective in reducing postischemic microcirculatory disturbances in models of renal, 72 cardiac, 73 and cerebral 74 I/R and we here show that, in combination with the nitric oxide donor L-arginine, it provides maximal improvement of the microcirculation after hepatic I/R. Second, agents that target the HIF-1␣ pathway, including 17-DMAG, are gaining increased attention as novel anticancer drugs.…”
Section: Discussionmentioning
confidence: 90%
“…In the past, several compounds that aim at restoring the endothelin-1/nitric oxide imbalance have been successfully applied to reduce microcirculatory disturbances and liver tissue damage. 18,19,54,70,71 Atrasentan is effective in reducing postischemic microcirculatory disturbances in models of renal, 72 cardiac, 73 and cerebral 74 I/R and we here show that, in combination with the nitric oxide donor L-arginine, it provides maximal improvement of the microcirculation after hepatic I/R. Second, agents that target the HIF-1␣ pathway, including 17-DMAG, are gaining increased attention as novel anticancer drugs.…”
Section: Discussionmentioning
confidence: 90%
“…However, it is unknown what upstream signaling may lead to AQP4 expression changes in astrocytes after CNS injury. It has been reported that exposing the brain to hypo-osmotic shock increases AQP4 protein levels (Vajda et al, 2000), and that endothelin-1, which increases after stroke, induces AQP4 expression and edema (Lo et al, 2005). Zhao et al (2005) shows that sulforaphane, an antioxidant gene activator, can also stimulate AQP4 induction, which suggests that AQP4 expression may react to oxidative stress conditions in injured CNS.…”
Section: Sci-induced Changes In Aqp4 Expressionmentioning
confidence: 98%
“…Several groups have reported changes in AQP4 expression after brain injury, or in brain tumors (Vajda et al, 2000;Lo et al, 2005;Zhao et al, 2005;Saadoun et al, 2002). Brain injury, depending on the type, can induce up-or down-regulation of AQP4.…”
Section: Sci-induced Changes In Aqp4 Expressionmentioning
confidence: 99%
“…ET-1 receptors (A and B) are widely expressed in the endothelial cells of the cerebral microvasculature as well as in populations of neurons, astrocytes and microglia, and ET-1 is thought to mediate interactions between astrocytes and the cerebral microvasculature (31,32) that have an important role in ischemia or stroke-induced brain edema and injury (31). Ischemia induces upregulation of expression of ET-1/3 and its receptors-A/B in the rat cortex (33), and activation of ET-1 by ischemia induces brain edema via AQP4 in rat astrocytic end-feet (34). In the present study, hypobaric hypoxia-activated cortical ET-1 is also involved in cerebral edema and apoptosis through activation of both CRFR1 and NF-κB, suggesting that antagonists for CRFR1 and ET-1R might be appropriate for treating hypoxia-induced disorders.…”
Section: Discussionmentioning
confidence: 99%